Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Environmental DNA (eDNA) metabarcoding as a complementary monitoring tool in cetacean visual surveys: from broad to fine-scale spatial analysis in open waters - Miguel Álvarez-González; Camilo Saavedra; Josep Rotllant; Graham J. Pierce; Paula Gutiérrez-Muñoz; José Antonio Vázquez Bonales; Paula Suarez-Bregua (Marine Environmental Research, 2026)

The reproductive ecology of Loligo squids (Cephalopoda: Myopsida) in Lusitanian zoogeographical province - Vladimir Laptikhovsky; Ana Moreno; Daniel Oesterwind; Catalina Perales-Raya; Graham Pierce; Jean-Paul Robin; Ignacio Sobrino; Maria Valls; Roger Villanueva; Athena Allen; Esther Abad; Giambattista Bello; et al. (Regional Studies in Marine Science, 2025)

Derivation of a standardized index to explore spatial, seasonal and between-year variation of squid (Loligo spp.) abundance in the English Channel - Anna Marcout; Eric Foucher; Graham Pierce; Jean-Paul Robin (Fisheries Research, 2025)

Monitoring levels of polychlorinated biphenyls (PCBs) in three cetacean species stranded in Galicia (Spain), NE Atlantic - Paula Gutiérrez-Muñoz; Begoña Pérez-Fernández; Camilo Saavedra; Pablo Covelo; Paula Méndez-Fernández; Alfredo López; Lucía Viñas; Graham J. Pierce (Marine Pollution Bulletin, 2025)

What's on the menu? Diet of common minke whales (Balaenoptera acutorostrata) stranded on the Atlantic Iberian coast - Silvia S. Monteiro; Andreia Torres-Pereira; Marisa Ferreira; José V. Vingada; Lídia Nicolau; Marina Sequeira; Alfredo López; Pablo Covelo; Maria Inês Azevedo; Gema Hernandez-Milian; Graham J. Pierce; Catarina Eira (Marine Environmental Research, 2025)

Impact of environmental conditions on English Channel long-finned squid (Loligo spp.) recruitment strength and spatial location - Anna Marcout; Eric Foucher; Graham J. Pierce; Jean-Paul Robin (Frontiers in Marine Science, 2024)
The English Channel has the highest long-finned squid landings in the Northeast Atlantic, making squid one of the most valuable resources exploited by demersal fisheries operating in this area. This resource consists of two short-lived long-finned squid species: Loligo forbesii and L. vulgaris , which have a similar appearance (they are not distinguished by fishers) but differ in the timing of their life cycle: in L. forbesii , the recruitment peak occurs in July while in L. vulgaris recruitment peak occurs in November. The abundance and distribution of cephalopod species, such as Loligo spp., depends on favourable environmental conditions to support growth, reproduction and successful recruitment. This study investigated the role of several environmental variables (bottom temperature, salinity, current velocity, phosphate and chlorophyll concentrations) on recruitment biomass (in July for L. forbesii and November for L. vulgaris ), as based on environmental data for pre-recruitment period from the Copernicus Marine Service and commercial catches of French bottom trawlers during the recruitment period over the years 2000 to 2021. To account for non-linear relationship between environmental descriptors and the biological response, General Additive Models (GAM) were fitted to the data. Separate models were obtained to forecast L. vulgaris and L. forbesii biomass indices during their respective recruitment periods. These models explain a high percentage of variation in biomass indices (65.8% for L. forbesii and 56.7% for L. vulgaris ) and may be suitable to forecast the abundance (in terms of biomass) and spatial distribution of the resource. Such forecasts are desirable tools to guide fishery managers. Since these models can be fitted shortly before the start of the fishing season, their routine implementation would take place in real-time fishery management (as promoted by fishery scientists dealing with short-lived species).

Cetaceans of north-western continental Africa (Morocco to Liberia): diversity and distribution - Ana M. Correia; Marieta Mihova; Ágatha Gil; Cláudia Oliveira-Rodrigues; Luís Afonso; Raul Valente; Massimiliano Rosso; Isabel Sousa-Pinto; Graham J. Pierce (Frontiers in Marine Science, 2024)
The north-western coast of Africa is one of the most productive marine systems in the world, where a high diversity of cetacean species has been recorded. However, management of human activities that impact cetacean populations in the area is inadequate, in part due to poor knowledge on cetacean occurrence and the lack of systematic surveys. We reviewed existing knowledge on cetacean distribution between Morocco and Liberia and analyzed the spatial and temporal distribution of records, as well as species occurrence, further discussing the reported distribution ranges. The systematic literature review included 39 sources reporting on 36 species in the area, with a total of 2241 sightings and 2178 non-sighting records. Delphinus delphis (common dolphin) and Tursiops truncatus (bottlenose dolphin) are the two species with the highest number of sources reporting on them. This review reveals a spatially and temporally heterogeneous coverage of the area in the literature and published data on cetacean occurrence. In summary, although most of the compiled sources are recently published (2011-2020), the majority of records are from prior to 2000. In several range states, especially south of Senegal, little information is available. Therefore, the available information is unlikely to represent the current status of cetacean communities in the region. It is essential to fill knowledge gaps by increasing the collection of cetacean distribution data in the area, in order to support effective conservation measures and ensure sustainable utilization of the living marine resources in this rapidly developing region.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Completing the picture: using vertebrae as well as otoliths in diet analysis reveals new preferred prey of great skuas - Susanna Quer; Graham John Pierce; Cristian N. Waggershauser; Lucy Gilbert (Marine Biology, 2024)
Knowledge of the diet of marine predators such as seabirds is fundamental to understanding the ecological cascades they may influence and the impact that environmental changes may have on them. Diet analysis of seabirds frequently relies on the identification of fish otoliths in pellets. However, it is recognised that the true dietary importance of fish with small and fragile otoliths is likely underestimated, requiring an additional method. In this study, we compared the identification of otoliths with that of vertebrae in pellets to gain a more complete picture of seabird diet. We identified fish otoliths and vertebrae from 2584 great skua Stercorarius skua pellets collected between 2014 and 2017 from five colonies in Scotland. Diet varied markedly between colonies, comprising mostly fish in Shetland and mostly birds in St Kilda. 10% of pellets contained otoliths compared to 70% with fish vertebrae. Atlantic herring Clupea harengus and Atlantic mackerel Scomber scombrus were the most common fish species at all colonies when using vertebrae in contrast to being virtually absent when using otoliths. Conversely, the occurrence of Norway pout Trisopterus esmarkii and pollock Pollachius pollachius otoliths was six and eight times, respectively, higher than for vertebrae. Therefore, combining data from both otoliths and vertebrae provides a more complete profile of the fish component of seabird diet. This is fundamental to improving our understanding of the impacts of marine management policies on seabirds, as well as how changes in the population size of such seabird species might affect their prey species.

Using fusion effects to decrease uncertainty in distance sampling models when collating data from different surveys - Floriane Plard; Hélder Araújo; Amaia Astarloa; Maite Louzao; Camilo Saavedra; José Antonio Vazquez Bonales; Graham John Pierce; Matthieu Authier (Marine Mammal Science, 2024)
Estimates of population abundance are required to study the impacts of human activities on populations and assess their conservation status. Despite considerable effort to improve data collection, uncertainty around estimates of cetacean densities can remain large. A fundamental concept underlying distance sampling is the detection function. Here we focus on reducing the uncertainty in the estimation of detection function parameters in analyses combining data sets from multiple surveys, with known effects on the precision of density estimates. We developed detection functions using infinite mixture models that can be applied on data collating multiple species and/or surveys. These models enable automatic clustering by fusing the species and surveys with similar detection functions. We present a simulation analysis of a multisurvey data set in a Bayesian framework where we demonstrated that distance sampling models including fusion effects showed lower uncertainty than classical distance sampling models. We illustrated the benefits of this new model using data of line transect surveys from the Bay of Biscay and Iberian Coast. Future estimates of abundance using conventional distance sampling models on large multispecies surveys or on data sets combining multiple surveys could benefit from this new model to provide more precise density estimates.

Estimating fishing effort and LPUE for the Scottish brown crab (Cancer pagurus) trap fishery using VMS and observer data - Carlos Mesquita; Helen Dobby; Catherine S. Jones; Graham J. Pierce (Fisheries Research, 2024)

Age and growth analysis of Loliginidae squid paralarvae in the NW Spanish coast using statolith increment counts - Elsa García-Mayoral; Álvaro Roura; Graham J. Pierce; Ángel F. González (Marine Biology, 2024)
Knowledge of recruitment to a fishery is particularly important in short-lived species, like most cephalopods, in which there is a complete turnover of individual every 1 or 2 years. In this study, age, body length, statolith length and growth rates of loliginid paralarvae ( Alloteuthis media , A. subulata and Loligo vulgaris ) were determined to evaluate the form of the growth curve and differences between species and hatching seasons. A total of 222 paralarvae collected in zooplankton samples along the Galician coast (NW Spain) were used to determine relationships between dorsal mantle length (DML), statolith length (SL) and the number of increments (NI)) deposited in the statolith. The paralarvae of L. vulgaris were between 1 and 35 days old, while both Alloteuthis species ranged in age from 1 to 54 days . Generalised additive models (GAMs) revealed non-linear growth in DML, with L. vulgaris exhibiting higher DML-at-age than Alloteuthis species. The best parametric model fit for these data was obtained using exponential regressions. The SL–NI relationship also differed between species, with L. vulgaris having larger statolith length at age . The paralarvae of L. vulgaris and A. media had two well-differentiated hatching peaks, one in late spring-early summer (beginning of the upwelling season) and another peak in late autumn (end of the upwelling season). Alloteuthis subulata had an earlier hatching peak in spring than in the other two loliginid species—and the second peak in autumn was barely visible, possibly because this species occurs further north in areas not sampled in autumn.

Towards global traceability for sustainable cephalopod seafood - Ian G. Gleadall; Hassan Moustahfid; Warwick H. H. Sauer; Lahsen Ababouch; Alexander I. Arkhipkin; Jilali Bensbai; Isa Elegbede; Abdelmalek Faraj; Pedro Ferreiro-Velasco; Roberto González-Gómez; Carmen González-Vallés; Unai Markaida; et al. (Marine Biology, 2024)

Identifying sustainability priorities among value chain actors in artisanal common octopus fisheries - Gillian B. Ainsworth; Pablo Pita; Cristina Pita; Katina Roumbedakis; Graham J. Pierce; Catherine Longo; Gregory Verutes; Tereza Fonseca; Daniela Castelo; Carlos Montero-Castaño; Julio Valeiras; Francisco Rocha; et al. (Reviews in Fish Biology and Fisheries, 2023)
The United Nations (UN) Decade of Ocean Science highlights a need to improve the way in which scientific results effectively inform action and policies regarding the ocean. Our research contributes to achieving this goal by identifying practical actions, barriers, stakeholder contributions and resources required to increase the sustainability of activities carried out in the context of artisanal fisheries to meet UN Sustainable Development Goals (SDG) and International Year of Artisanal Fisheries and Aquaculture (IYAFA) Global Action Plan (GAP) Pillar targets. We conducted a novel ‘social value chain analysis’ via a participatory workshop to elicit perspectives of value chain actors and fisheries stakeholders associated with two Spanish artisanal common octopus ( Octopus vulgaris ) fisheries (western Asturias—Marine Stewardship Council [MSC] certified, and Galicia—non-MSC certified) about their priorities regarding sustainable octopus production and commercialization. Our adapted Rapfish sustainability framework emphasised the importance of economic, environmental, ethical, institutional, social, and technological indicators to different actors across the value chain. We mapped participants’ shared sustainability priorities (e.g. integrated fisheries management, knowledge-based management, product traceability) to six Rapfish indicators, seven IYAFA Pillars and twelve SDGs to reveal how our results can inform ocean policy and actions. This identified how certification incentives and other cooperative approaches can facilitate environmental, economic and social sustainability (e.g. value-added products, price premiums for producers, gender inclusive organisations); support IYAFA priority outcomes (raised awareness, strengthened science-policy interface, empowered stakeholders, partnerships); and help to achieve UN SDG targets (e.g. SDG 14.b, SDG 17.17). The results can inform actors, stakeholders and policymakers about how different actors contribute to efforts to achieve the SDGs and how to manage priorities for sustainable actions within artisanal fisheries and their value chains. We recommend inclusive and equitable participatory knowledge transfer and governance platforms as part of the UN Decade of Ocean Science and beyond where participants can create theories of change towards sustainability involving the development of multi-sectoral ocean policies framed at the level of the value chain and supported by appropriate governance structures. Graphical Abstract

Response of cetaceans to fluctuations of pelagic fish stocks and environmental conditions within the Celtic Sea ecosystem - Andrea Fariñas-Bermejo; Simon Berrow; Michaël Gras; Ciaran O’Donnell; Vasilis Valavanis; Dave Wall; Graham J. Pierce (Frontiers in Marine Science, 2023)
Inshore waters off the south coast of Ireland are an important foraging area for a range of cetacean species. Some of the main prey species of these cetaceans are herring and sprat, two economically valuable fish species in the region. The Celtic Sea herring stock suffered a marked decline in 2013. The present study aimed to investigate potential changes in the ecosystem associated to the herring decline and to determine the potential impacts on predators. Here we analyzed sightings information of common dolphins, fin, minke, humpback and unidentified whale species, acoustic data of herring and sprat, and a range of environmental variables mainly derived from satellites. Firstly, we characterized spatio-temporal patterns in the relative abundance of predator and prey species, and environmental variables, and compared periods before and since the herring decline. Since the 2013 herring decline, (i) the herring stock has mainly concentrated in south-eastern coastal waters and southern offshore Irish waters, (ii) sprat density has increased, (iii) chlorophyll concentration has decreased, (iv) sea surface temperature has risen, and (v) the euphotic layer has extended deeper. Secondly, we modelled the effects of prey density and environmental conditions on the relative abundance and distribution of cetaceans, as well as the effects of environmental conditions on prey density, between 2005-2018 by applying Hurdle Generalized Additive Models. The models for herring and sprat support the idea that these species have different environmental relationships, for example herring tended to be found in shallower waters than was the case for sprat. The presence and relative abundance of common dolphins were significantly affected by both environmental conditions and herring density, whereas whale species presence and relative abundance were found to be correlated with sea surface temperature and prey density. The model results suggest differences in prey choice among whale species. Understanding the dynamic relationships between predators, prey and the environment is important to inform an ecosystem-based approach to fisheries management.

Trophic ecology of the squid Doryteuthis gahi in the Southwest Atlantic inferred from stable isotope analysis - Tobias Büring; Jessica B. Jones; Graham Pierce; Francisco Rocha; Paco Bustamante; Maud Brault-Favrou; Alexander I. Arkhipkin (Estuarine, Coastal and Shelf Science, 2023)

Cephalopods, a gap in the European Marine Strategy Framework Directive and their future integration - Bianca T. C. Bobowski; Anne Marie Power; Graham J. Pierce; Ana Moreno; Ane Iriondo; Julio Valeiras; Inna M. Sokolova; Daniel Oesterwind (Marine Biology, 2023)
With the aim of maintaining or obtaining good environmental status in the Northeast Atlantic and northern Mediterranean Sea, the European Marine Strategy Framework Directive (EU-MSFD) came into force in 2008. All EU Member States (MS) have the task of assessing the current state of their adjacent waters to guarantee sustainable use of marine resources and healthy ecosystems for the current and future generations. Although the MSFD has been implemented for over a decade, there are still gaps in the assessment of various ecologically and commercially important marine species, such as cephalopods. Here we describe the status of cephalopods, a key component of marine ecosystems and a valuable fishing resource, within the MSFD. To do so, we review how MS deal with this group in their reporting and identify and explain the gaps in the cephalopod assessment. We describe the main challenges including the limited data and the rarity of dedicated surveys on cephalopods. However, we argue that cephalopods can be partially integrated into the EU-MSFD assessment, illustrating the current opportunities and future possibilities of their integration into the MSFD, mainly using Descriptors 1–4. Graphical abstract

Diet of striped dolphins ( Stenella coeruleoalba ) in southern Spanish waters - Camilo Saavedra; Manuel García‐Polo; Joan Giménez; José Luis Mons; Juan José Castillo; Carolina Fernández‐Maldonado; Renaud de Stephanis; Graham John Pierce; María Begoña Santos (Marine Mammal Science, 2022)
Identifiable food remains were analyzed from 46 stomachs of striped dolphins ( Stenella coeruleoalba ) stranded in southern Spain between 2007 and 2014. Results suggest that the species feeds mainly on mesopelagic and neritic fish, but also on oceanic squids. Fish species of the family Myctophidae were the main prey in terms of numerical importance and reconstructed prey weight (62% N and 29% W), followed by squids of the family Ommastrephidae (20% W) and bogue ( Boops boops ) (15% W). The most important prey taxa according to the General Importance Index (GII) were C. maderensis , Ommastrephidae gen. spp., Notoscopelus spp., and M. punctatum . Higher number of mesopelagic myctophids were found in dolphins from the Mediterranean (73% vs. 29% N), while more demersal gobiids and European hake ( Merluccius merluccius ) were found in those from the Atlantic (44% vs. 1% and 8% vs.

Environmental DNA (eDNA) for monitoring marine mammals: Challenges and opportunities - Paula Suarez-Bregua; Miguel Álvarez-González; Kim M. Parsons; Josep Rotllant; Graham J. Pierce; Camilo Saavedra (Frontiers in Marine Science, 2022)
Monitoring marine mammal populations is essential to permit assessment of population status as required by both national and international legislation. Traditional monitoring methods often rely on visual and/or acoustic detections from vessels and aircraft, but limitations including cost, errors in the detection of some species and dependence on taxonomic expertise, as well as good weather and visibility conditions often limit the temporal and spatial scale of effective, long-term monitoring programs. In recent years, environmental DNA (eDNA) has emerged as a revolutionary tool for cost-effective, sensitive, non-invasive species monitoring in both terrestrial and aquatic realms. eDNA is a rapidly developing field and a growing number of studies have successfully implemented this approach for the detection and identification of marine mammals. Here, we review 21 studies published between 2012 and 2021 that employed eDNA for marine mammal monitoring including single species detection, biodiversity assessment and genetic characterization. eDNA has successfully been used to infer species presence (especially useful for rare, elusive or threatened species) and to characterize the population genetic structure, although additional research is needed to support the interpretation of non-detections. Finally, we discuss the challenges and the opportunities that eDNA could bring to marine mammal monitoring as a complementary tool to support visual and acoustic methods.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Patterns and Trends in Cetacean Occurrence Revealed by Shorewatch, a Land-Based Citizen Science Program in Scotland (United Kingdom) - Paula Gutiérrez-Muñoz; Alice E. M. Walters; Sarah J. Dolman; Graham J. Pierce (Frontiers in Marine Science, 2021)
Shorewatch is a citizen science project, managed by Whale and Dolphin Conservation (WDC), that records the occurrence of cetaceans during regular, standardized watches from a series of locations along the coast of Scotland (United Kingdom). Observer training and a clearly defined protocol help deliver a valuable source of information about cetacean occurrence and activity along the coast. Between 2005–2018, over 52000 watches generated over 11000 sightings of at least 18 cetacean species. Generalized Additive Models based on sightings for the five most commonly sighted species (bottlenose dolphin, harbor porpoise, minke whale, Risso’s dolphin, and common dolphin), at those sites with the longest time series, demonstrated seasonal, geographical and year-to-year differences in their local occurrence and relative abundance. Bottlenose dolphins are mainly present at observation sites located on the east coast of Scotland, being uncommon on the west coast, while harbor porpoise and minke whale are principally present at sites located on the west coast. The seasonality observed in cetacean occurrence is consistent with peak abundance in summer months described by previous studies in the area. Mean depth around the observation sites is the static variable that apparently has the greatest influence on species presence and number of sightings, except for Risso’s dolphin. All the species except bottlenose dolphin showed upward trends in occurrence and number of sightings over the period 2012–2018. Evidence of temporal autocorrelation was found between results from consecutive watches at the same site on the same day as well as between results from consecutive days at the same site. The power to detect declines in local abundance over a 6-year period depends on the underlying sighting rate of each cetacean species, the number of watches performed and the rate of decline. Simulations performed to determine the power to detect a decline suggest that the current intensity of observation effort in some observation sites, of about 2500 watches per year, may offer good prospects of detecting a 30% decline of the most frequently sighted species (95% of the time) over a 6-year period, although a more even distribution of observation effort in space and time is desirable. The data could potentially be used for monitoring and 6-yearly reporting of the status of cetacean populations.

Ecological-Fishery Forecasting of Squid Stock Dynamics under Climate Variability and Change: Review, Challenges, and Recommendations - Hassan Moustahfid; Lisa C. Hendrickson; Alexander Arkhipkin; Graham J. Pierce; Avijit Gangopadhyay; Hideaki Kidokoro; Unai Markaida; Chingiz Nigmatullin; Warwick H. Sauer; Patrizia Jereb; Gretta Pecl; Thibaut de la Chesnais; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Predicting Cetacean Distributions in the Eastern North Atlantic to Support Marine Management - Ana M. Correia; Diana Sousa-Guedes; Ágatha Gil; Raul Valente; Massimiliano Rosso; Isabel Sousa-Pinto; Neftalí Sillero; Graham J. Pierce (Frontiers in Marine Science, 2021)
Data on species occurrence at the scale of their distributional range and the determination of their habitat use requirements are essential to support conservation and define management plans that account for their habitat requirements. For wide-ranging species, such as cetaceans, especially considering that their marine habitats include offshore areas, collection of such data is challenging. In the absence of dedicated surveys, alternative methodologies are needed, such as the use of data collected from platforms of opportunity and modelling techniques to predict distribution in unsurveyed areas. Using 6 years of cetacean occurrence data collected along cargo ship routes between the Iberian Peninsula, northwestern African coasts and the Macaronesian islands, we developed ecological niche models to assess habitat preferences and predict suitable habitats of the eight most frequently sighted cetacean taxa in the area. Explanatory variables used for model fitting included topographic, oceanographic, detectability, geographic and seasonal features. To provide a robust habitat characterisation, along with predictions of habitat suitability, making best use of occurrence datasets, we applied two modelling techniques, GAM and Maxent, which offer complementary strengths. Coastal areas provide important habitats for common and bottlenose dophins, while other dolphin species (spotted and striped dolphins) have a more oceanic distribution. The predicted niches of Cuvier’s beaked whale and minke whales are mainly in the high seas at northern latitudes. Suitable habitats for sperm whales and pilot whales are mostly in southern areas in continental slope regions. For all the species, models indicated that areas around seamount features offer suitable habitats, likely of high relevance in oligotrophic offshore waters. As such, dedicated survey effort in such areas would facilitate development and implementation of appropriate management plans, which are currently lacking. Our models offer an important contribution to baseline knowledge of cetacean distribution at basin-scale in the region and could support the definition of priority areas, monitoring plans, and conservation measures, essential to comply with the requirements of the EU Marine Strategy Framework Directive.

Spiral valve parasites of blue and common thresher sharks as indicators of shark feeding behaviour and ecology - Antonella Preti; Ken MacKenzie; Kate A. Spivey; Leslie R. Noble; Catherine S. Jones; Ralph G. Appy; Graham J. Pierce (Journal of Fish Biology, 2020)
This study documented the parasite faunas of the spiral valves of blue sharks Prionace glauca (L. 1758) and common thresher sharks Alopias vulpinus (Bonnaterre, 1788) caught in the California Current Large Marine Ecosystem (CCLME) north of the Mexican border. The spiral valves of 18 blue and 19 thresher sharks caught in the CCLME from 2009 to 2013 were examined for parasites. Seven parasite taxa were found in blue sharks and nine in threshers. The tetraphyllidean cestode Anthobothrium sp. (78% prevalence) was the most common parasite in blue sharks, and the phyllobothriid cestode Paraorygmatobothrium sp. (90% prevalence) was the most common in threshers. An adult nematode of the genus Piscicapillaria was found in threshers for the first time and may be a new species. Adult individuals of Hysterothylacium sp. were found in both shark species. The adult acanthocephalan Rhadinorhynchus cololabis and remains of the parasitic copepod Pennella sp. – both parasites of Pacific saury, Cololabis saira – were found in the intestines of threshers, indicating recent feeding on saury. This study paves the way for a more comprehensive examination, including more samples and a wider variety of shark species, to provide a greater understanding of shark feeding behaviour and possibly provide information on shark population biology.

Cultures of Gossypium barbadense cotton ovules offer insights into the microtubule-mediated control of fiber cell expansion - Ethan T. Pierce; Benjamin P. Graham; Michael R. Stiff; Jason A. Osborne; Candace H. Haigler (Planta, 2019)

Size-dependent change in body shape and its possible ecological role in the Patagonian squid (Doryteuthis gahi) in the Southwest Atlantic - Jessica B. Jones; Graham J. Pierce; Fran Saborido-Rey; Paul Brickle; Frithjof C. Kuepper; Zhanna N. Shcherbich; Alexander I. Arkhipkin (Marine Biology, 2019)

Barcoding and morphometry to identify and assess genetic population differentiation and size variability in loliginid squid paralarvae from NE Atlantic (Spain) - Lorena Olmos-Pérez; Graham J. Pierce; Álvaro Roura; Ángel F. González (Marine Biology, 2018)

Feeding ecology of the common dolphin (Delphinus delphis) in Western Iberian waters: has the decline in sardine (Sardina pilchardus) affected dolphin diet? - Ana Marçalo; Lídia Nicolau; Joan Giménez; Marisa Ferreira; Jorge Santos; Hélder Araújo; Alexandra Silva; José Vingada; Graham J. Pierce (Marine Biology, 2018)

First record on stranding of a live giant squid Architeuthis dux outside Japanese waters - Angel Guerra; Ángel F. González; Graham J. Pierce (Ecology, 2018)

Sepiolid paralarval diversity in a regional upwelling area of the NE Atlantic - Lorena Olmos-Pérez; Álvaro Roura; Graham J. Pierce; Ángel F. González (Hydrobiologia, 2018)

Vocal foragers and silent crowds: context-dependent vocal variation in Northeast Atlantic long-finned pilot whales - Fleur Visser; Annebelle C.M. Kok; Machiel G. Oudejans; Lindesay A.S. Scott-Hayward; Stacy L. DeRuiter; Ana C. Alves; Ricardo N. Antunes; Saana Isojunno; Graham J. Pierce; Hans Slabbekoorn; Jef Huisman; Patrick J. O. Miller (Behavioral Ecology and Sociobiology, 2017)

Factors driving patterns and trends in strandings of small cetaceans - Camilo Saavedra; Graham J. Pierce; Jesús Gago; Dunja Jusufovski; Águeda Cabrero; Santiago Cerviño; Alfredo López; Jose A. Martínez-Cedeira; M. Begoña Santos (Marine Biology, 2017)

Effects of vessel traffic on relative abundance and behaviour of cetaceans: the case of the bottlenose dolphins in the Archipelago de La Maddalena, north-western Mediterranean sea - Maria Grazia Pennino; M. Amparo Pérez Roda; Graham J. Pierce; Andrea Rotta (Hydrobiologia, 2016)

Major Histocompatibility Complex (MHC) class II sequence polymorphism in long-finned pilot whale ( Globicephala melas ) from the North Atlantic - Sílvia S. Monteiro; José V. Vingada; Alfredo López; Graham J. Pierce; Marisa Ferreira; Andrew Brownlow; Bjarni Mikkelsen; Misty Niemeyer; Robert J. Deaville; Catarina Eira; Stuart Piertney (Marine Biology Research, 2016)

Generic skills needs for graduate employment in the aquaculture, fisheries and related sectors in Europe - Cristina Pita; Margaret Eleftheriou; Jaime Fernández-Borrás; Susana Gonçalves; Eleni Mente; M. Begoña Santos; Sónia Seixas; Graham J. Pierce (Aquaculture International, 2015)

Marine mammals and good environmental status: science, policy and society; challenges and opportunities - Maria Begoña Santos; Graham John Pierce (Hydrobiologia, 2015)

Do pingers cause stress in fish? An experimental tank study with European sardine, Sardina pilchardus (Walbaum, 1792) (Actinopterygii, Clupeidae), exposed to a 70 kHz dolphin pinger - Sabine Goetz; M. Begoña Santos; José Vingada; Damián Costas Costas; Antonio González Villanueva; Graham John Pierce (Hydrobiologia, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Interaction between bottlenose dolphin (Tursiops truncatus) and trammel nets in the Archipelago de La Maddalena, Italy - M. Grazia Pennino; A. Rotta; Graham J. Pierce; José M. Bellido (Hydrobiologia, 2015)

Life history of harbor porpoises ( Phocoena phocoena ) in Scottish ( UK ) waters - Jennifer A. Learmonth; Sinead Murphy; Patricia L. Luque; Robert J. Reid; I. Anthony P. Patterson; Andrew Brownlow; Harry M. Ross; Jason P. Barley; M. Begoña Santos; Graham J. Pierce (Marine Mammal Science, 2014)
Life history parameters were determined for stranded and bycaught harbor porpoises ( Phocoena phocoena ) from Scottish ( UK ) waters (1992–2005). Fetal growth rate was 84.4 mm/mo and mean size at birth was 76.4 cm (range 65–88 cm). Males and females had a similar range of body lengths (65–170 cm and 66–173 cm, respectively), although asymptotic lengths were higher in females than males (approximately 158 cm and 147 cm, respectively). Nonpregnant females were significantly lighter, in relation to their length than males. Maximum estimated age was 20 yr for both sexes. Age at sexual maturity ( ASM ) was estimated as 4.35 yr in females and 5.00 yr in males. Conception occurred mainly in July and August although reproductively active males were recorded during April to July. Gestation lasted 10–11 mo, with calving mainly between May and July. Lactating females were recorded during June to November, while small calves with solid food in their stomachs were found mainly during February to May. Estimated pregnancy rate (0.34–0.40) is lower than recorded elsewhere, but is likely underestimated due to the prevalence of mature females of poor health status in the sample. Nevertheless, cetacean strandings can be an essential source of data on demographic parameters.

Predicting population‐level risk effects of predation from the responses of individuals - Colin D. MacLeod; Ross MacLeod; Jennifer A. Learmonth; Will Cresswell; Graham J. Pierce (Ecology, 2014)
Fear of predation produces large effects on prey population dynamics through indirect risk effects that can cause even greater impacts than direct predation mortality. As yet, there is no general theoretical framework for predicting when and how these population risk effects will arise in specific prey populations, meaning that there is often little consideration given to the key role predator risk effects can play in understanding conservation and wildlife management challenges. Here, we propose that population predator risk effects can be predicted through an extension of individual risk trade‐off theory and show for the first time that this is the case in a wild vertebrate system. Specifically, we demonstrate that the timing (in specific months of the year), occurrence (at low food availability), cause (reduction in individual energy reserves), and type (starvation mortality) of a population‐level predator risk effect can be successfully predicted from individual responses using a widely applicable theoretical framework (individual‐based risk trade‐off theory). Our results suggest that individual‐based risk trade‐off frameworks could allow a wide range of population‐level predator risk effects to be predicted from existing ecological theory, which would enable risk effects to be more routinely integrated into consideration of population processes and in applied situations such as conservation.

Including cetaceans in multi-species assessment models using strandings data: why, how and what can we do about it? - Saavedra Camilo; Cabrero Agueda; Cedeira Jose; Cerviño Santiago; Gago Jesus; González-Nuevo Gonzalo; Howell Daniel; López Alfredo; Pierce Graham; Read Fiona; Santos M. Begoña (Frontiers in Marine Science, 2014)

Patterns and trends in the diet of long‐finned pilot whales ( Globicephala melas ) in the northeast Atlantic - M. Begoña Santos; Silvia S. Monteiro; José V. Vingada; Marisa Ferreira; Alfredo López; José A. Martínez Cedeira; Robert J. Reid; Andrew Brownlow; Graham J. Pierce (Marine Mammal Science, 2014)
There is little previous information on feeding habits of long‐finned pilot whales ( Globicephala melas ) in the northeast Atlantic. The present study analyzed stomach contents of pilot whales stranded in Portugal ( n = 6), Galicia (northwest Spain) ( n = 32), and Scotland (United Kingdom) ( n = 10), from 1990 to 2011. These animals ranged from 213 to 555 cm in length (24 females, 19 males and 5 of unknown sex). The main prey identified were cephalopods of the families Octopodidae and Ommastrephidae, the former being numerically more important in Iberia (Portugal and Galicia) and the latter more important in Scotland, with Iberian whales also showing a more diverse diet. Multivariate analysis revealed evidence of geographical and seasonal variation in diet. Generalized Additive Modeling results indicated that more octopus ( Eledone cirrhosa ) were eaten in Iberia than in Scotland, more in the first half of the year, and more in larger whales. Numbers of ommastrephid squids in the stomach decreased over the study period and varied with season and whale length. This study confirms cephalopods as the main prey of pilot whales, as previously reported, although our results also suggest that, in the northeast Atlantic, ommastrephid squid are largely replaced as the main prey by octopods at lower latitudes.

Ecological niche segregation among five toothed whale species off the NW Iberian Peninsula using ecological tracers as multi-approach - Paula Méndez-Fernandez; Graham J. Pierce; Paco Bustamante; Tiphaine Chouvelon; Marisa Ferreira; Angel F. González; Alfredo López; Fiona L. Read; M. Begoña Santos; Jérôme Spitz; José V. Vingada; Florence Caurant (Marine Biology, 2013)

Population structure and residency of whale sharks Rhincodon typus at Utila, Bay Islands, Honduras - S. Fox; I. Foisy; R. De La Parra Venegas; B. E. Galván Pastoriza; R. T. Graham; E. R. Hoffmayer; J. Holmberg; S. J. Pierce (Journal of Fish Biology, 2013)
There were 479 reported whale shark Rhincodon typus encounters between 1999 and 2011 at the island of Utila, which forms part of the Meso‐American Barrier Reef System ( MBRS ) in the western Caribbean Sea. The majority of R. typus were found to feed on small bait fish associated with various tuna species. Ninety‐five individual R. typus , ranging from 2 to 11 m total length ( L T ), were identified through their unique spot patterns. A significant male bias (65%) was present. There was no significant difference between the mean ± s.d . L T of female (6·66 ± 1·65 m) and male (6·25 ± 1·60 m) R. typus . Most R. typus were transient to Utila, with 78% sighted only within a single calendar year, although some individuals were sighted in up to 5 years. Mean residency time was modelled to be 11·76 days using maximum likelihood methods.

Fishery discards and bycatch: solutions for an ecosystem approach to fisheries management? - Jose M. Bellido; M. Begoña Santos; M. Grazia Pennino; Xulio Valeiras; Graham J. Pierce (Hydrobiologia, 2011)

Preface: European Commission’s Marie Curie Action ECOSUMMER - Graham J. Pierce; Vasilis D. Valavanis; M. Begoña Santos; Julio M. Portela (Hydrobiologia, 2011)

Spatiotemporal patterns of marine mammal distribution in coastal waters of Galicia, NW Spain - Evangelos Spyrakos; Tania C. Santos-Diniz; Gema Martinez-Iglesias; Jesus M. Torres-Palenzuela; Graham J. Pierce (Hydrobiologia, 2011)

Temporal and ontogenetic variation in the diet of squid (Loligo forbesii Streenstrup) in Scottish waters - Sansanee Wangvoralak; Lee C. Hastie; Graham J. Pierce (Hydrobiologia, 2011)

Environmental drivers of the anchovy/sardine complex in the Eastern Mediterranean - Isidora Katara; Graham J. Pierce; Janine Illian; Beth E. Scott (Hydrobiologia, 2011)

Fine-scale genetic structure of bottlenose dolphins, Tursiops truncatus, in Atlantic coastal waters of the Iberian Peninsula - Ruth Fernández; M. Begoña Santos; Graham J. Pierce; Ángela Llavona; Alfredo López; Mόnica A. Silva; Marisa Ferreira; Manuel Carrillo; Pablo Cermeño; Santiago Lens; Stuart B. Piertney (Hydrobiologia, 2011)

Patterns of investment in reproductive and somatic tissues in the loliginid squid Loligo forbesii and Loligo vulgaris in Iberian and Azorean waters - Jennifer M. Smith; Graham J. Pierce; Alain F. Zuur; Helen Martins; M. Clara Martins; Filipe Porteiro; Francisco Rocha (Hydrobiologia, 2011)

An overview of commercial fishers’ attitudes towards marine protected areas - Cristina Pita; Graham J. Pierce; Ioannis Theodossiou; Karen Macpherson (Hydrobiologia, 2011)

Stable isotope analysis in two sympatric populations of bottlenose dolphins Tursiops truncatus: evidence of resource partitioning? - Ruth Fernández; Susana García-Tiscar; M. Begoña Santos; Alfredo López; Jose A. Martínez-Cedeira; Jason Newton; Graham J. Pierce (Marine Biology, 2011)

Risso's dolphins alter daily resting pattern in response to whale watching at the Azores - Fleur Visser; Karin L. Hartman; Ente J. J. Rood; Arthur J. E. Hendriks; Daan B. Zult; Wim J. Wolff; Jef Huisman; Graham J. Pierce (Marine Mammal Science, 2011)
Behavioral responses of Risso's dolphins ( Grampus griseus ) to whale watching vessels were studied off Pico Island, Azores. Dolphin behavior was studied from a land‐based lookout, enabling observations of groups in the absence and presence of vessels. The number of whale watching vessels showed a clear seasonal pattern, dividing the whale watching period into a low season and a high season. During the low season, Risso's dolphins rested mainly in the morning and afternoon. During the high season, Risso's dolphins rested less and did so mainly at noon, when the number of active vessels was lowest. Data analysis using a generalized additive mixed model indicated that this change in resting behavior was associated with vessel abundance. When more than five vessels were present, Risso's dolphins spent significantly less time resting and socializing. During the high season, this vessel abundance was exceeded during 20% of observation days. While we cannot be sure that the observed changes in behavior have fitness consequences for Risso's dolphins, reduced resting and socializing rates can have negative impacts on the build‐up of energy reserves and on reproductive success. We suggest the adoption of precautionary management measures to regulate the timing and intensity of whale watching activities.

Spatiotemporal coupling/decoupling of planktonic larvae and benthic settlement in decapods in the Scottish east coast - Maria Pan; Graham J. Pierce; Carey O. Cunningham; Steve J. Hay (Marine Biology, 2011)

Comparison of two histological techniques for age determination in small cetaceans - Patricia Lastra Luque; Jennifer A. Learmonth; M. Begoña Santos; Elena Ieno; Graham J. Pierce (Marine Mammal Science, 2009)
Age estimation in odontocetes is based on counts of growth layer groups (GLGs) deposited in recording structures such as teeth. Generally, tooth sections are obtained using a cryostat microtome. However, some researchers prefer obtaining thin sections using a traditional paraffin microtome. Little information is available on the application of this technique to dolphin teeth. Our main aim was to investigate if the paraffin technique can be a viable alternative. We considered whether estimated age would be affected by preparation technique, staining method, and section thickness, while controlling for effects of species, body length, and sex. We also analyzed whether the staining method would affect readability of GLGs and age reading variability. Teeth from 86 individuals (representing seven species) were used, but not all were prepared using both techniques because sufficient teeth were not available in all cases. Although the staining method had significant effects on the estimated age using both techniques, the variability of GLG counts was small and appeared to be similar for both techniques. Using Mayer's hematoxylin stained sections of 8 μm thickness, good agreement of ages was obtained from both techniques, with more preparations classified as “good quality” for the paraffin technique. Mayer's hematoxylin provided the best contrast of the GLGs when using the paraffin technique. We conclude that the paraffin technique is viable and represents a cost‐effective alternative to a cryostat microtome when preparing cetacean teeth for age determination.

Species effects on ecosystem processes are modified by faunal responses to habitat composition - Mark T. Bulling; Martin Solan; Kirstie E. Dyson; Gema Hernandez-Milian; Patricia Luque; Graham J. Pierce; Dave Raffaelli; David M. Paterson; Piran C. L. White (Oecologia, 2008)

Do ovarian scars persist with age in all Cetaceans: new insight from the short-beaked common dolphin (Delphinus delphis Linnaeus, 1758) - Willy Dabin; François Cossais; Graham J. Pierce; Vincent Ridoux (Marine Biology, 2008)

Results of a short study of interactions of cetaceans and longline fisheries in Atlantic waters: environmental correlates of catches and depredation events - Gema Hernandez-Milian; Sabine Goetz; Catuxa Varela-Dopico; José Rodriguez-Gutierrez; Jorge Romón-Olea; José R. Fuertes-Gamundi; Edelmiro Ulloa-Alonso; Nick J. C. Tregenza; Andy Smerdon; Monserrat G. Otero; Vicente Tato; Jianjun Wang; et al. (Hydrobiologia, 2008)

Modelling of essential fish habitat based on remote sensing, spatial analysis and GIS - Vasilis D. Valavanis; Graham J. Pierce; Alain F. Zuur; Andreas Palialexis; Anatoly Saveliev; Isidora Katara; Jianjun Wang (Hydrobiologia, 2008)

A comparison of approaches for modelling the occurrence of marine animals - Colin D. MacLeod; Laura Mandleberg; Caroline Schweder; Sarah M. Bannon; Graham J. Pierce (Hydrobiologia, 2008)

Atmospheric forcing on chlorophyll concentration in the Mediterranean - Isidora Katara; Janine Illian; Graham J. Pierce; Beth Scott; Jianjun Wang (Hydrobiologia, 2008)

A review of cephalopod–environment interactions in European Seas - Graham J. Pierce; Vasilis D. Valavanis; Angel Guerra; Patricia Jereb; Lydia Orsi-Relini; Jose M. Bellido; Isidora Katara; Uwe Piatkowski; João Pereira; Eduardo Balguerias; Ignacio Sobrino; Eugenia Lefkaditou; et al. (Hydrobiologia, 2008)

Identifying essential fish habitat for small pelagic species in Spanish Mediterranean waters - Jose M. Bellido; Alex M. Brown; Vasilis D. Valavanis; Ana Giráldez; Graham J. Pierce; Magdalena Iglesias; Andreas Palialexis (Hydrobiologia, 2008)

Real-time PCR assay for detection and relative quantification of Liocarcinus depurator larvae from plankton samples - Maria Pan; Alastair J. A. McBeath; Steve J. Hay; Graham J. Pierce; Carey O. Cunningham (Marine Biology, 2008)

Stable carbon and nitrogen isotope ratio profiling of sperm whale teeth reveals ontogenetic movements and trophic ecology - Sónia Mendes; Jason Newton; Robert J. Reid; Alain F. Zuur; Graham J. Pierce (Oecologia, 2007)

Growth strategies in the squid Loligo vulgaris from Portuguese waters - Ana Moreno; Manuela Azevedo; João Pereira; Graham J. Pierce (Marine Biology Research, 2007)

Effect of feed and feeding in the culture of salmonids on the marine aquatic environment: a synthesis for European aquaculture - Eleni Mente; Graham J. Pierce; Maria Begoña Santos; Christos Neofitou (Aquaculture International, 2006)

TAXONOMIC STATUS AND GEOGRAPHICAL CRANIAL VARIATION OF COMMON DOLPHINS ( DELPHINUS ) IN THE EASTERN NORTH ATLANTIC - Sinéad Murphy; Jerry S. Herman; Graham J. Pierce; Emer Rogan; Andrew C. Kitchener (Marine Mammal Science, 2006)
The common dolphin has a widespread distribution and is relatively abundant in the temperate to subtropical waters of the eastern North Atlantic. However, it is not known whether different species, subspecies, or populations occur in this region. We examined 393 common dolphin skulls obtained from both stranded and bycaught individuals collected between 1901 and 2005. The series included skulls of 152 females and 199 males, from animals ranging in body length from 93 to 230 cm and 105 to 244 cm, respectively. The ranges of total body length, skull size, RL/ZGW ratio and maximum upper alveolar (tooth) count of common dolphins in the eastern North Atlantic overlapped with those of both short‐ ( D. delphis ) and long‐beaked ( D. capensis ) species found off the Californian coast. However, in the absence of additional data, the common dolphin in the eastern North Atlantic is regarded here as a large form of Delphinus delphis . Sexual dimorphism and possible sex‐linked characters were identified within the sample. Results of the current study indicate some population differentiation within the eastern North Atlantic, with common dolphins off Portugal showing segregation in morphometric characteristics from common dolphins in other areas.

Bioaccumulation of Lead, Calcium and Strontium and their Relationships in the Octopus Octopus vulgaris - Sónia Seixas; Graham Pierce (Water, Air, & Soil Pollution, 2005)